The Effect of Destination Image and Electronic Word of Mouth on Visiting Decisions through Interest in Visiting the Twin Lakes Area Twin Lakes Region of West Sumatra - Dinda Azzahra; Arry Widodo; Anita Silvianita; Nurafni Rubiyanti (PT FORMOSA CENDEKIA GLOBAL, 2024)
Indonesia offers a unique travel experience with diverse cultures, religions, ethnicities and languages on each island. The Twin Lakes region in West Sumatra is one such amazing destination, despite experiencing a decline in visitation from 2019 to 2023. In the age of the internet and social media, advertising and electronic word of mouth (eWOM) can strengthen a destination's image, increase traveler interest and influence visiting decisions. The study used Structural Equation Modeling (SEM) to evaluate the influence of destination image and eWOM on interest in visiting the Twin Lakes Region. The implications of this research are important in building tourist interest and a positive image of this destination. By providing interesting information, we can influence tourists' decision to visit